Bias from enrollment: Peer effects on the academic performance of university students in PUCE-Ecuador - Guadalupe Duque, Melissa Pamela (2021)
This paper provides evidence of peer effects on academic achievement of university students in PUCE Ecuador, using a panel of academic-administrative data from students and each of their courses, for both semesters of 2018. To estimate the marginal effects of peer performance on individual academic achievement, a random effects model with controls is applied. The results show significant influence of the average group, high-achieving and low-achieving peers. Educational policy and course enrollment policies are discussed.